Leadership, Crisis Management, and Business Continuity - Alblooshi, Moosa Ahmed Jafar Almandoos; Mohamed, Ahmad Martadha; Yusr, Maha Mohammed (South Asian Journal of Social Sciences and Humanities, 2023)
The objective of the current research was to identify the mediating role of crisis management between leadership and business continuity. Crisis management has always been considered as a responsibility of the leaders of the organizations. Moreover, leaders have to show their true leadership skills during the time of crisis in order to keep things going. For meeting the objectives of the study, the data has been collected from 384 employees working at public sector organizations of UAE. The data has been collected by applying survey techniques and self administered questionnaires were distributed using simple random sampling. The findings from structural equation modelling revealed that leadership has a significant direct impact over business continuity as well as crisis management. this shows that leaders that are efficient in leadership holds the capability to manage the crisis. Moreover, the mediating role of crisis management between leadership and business continuity is also significant.